Outcomes of ICU Admission of Patients With Progressive Metastatic Gastrointestinal Cancer. (March 2020) - Epstein, Andrew S.; Yang, Andrew; Colbert, Lauren E.; Voigt, Louis P.; Meadows, Jason; Goldberg, Jessica I.; Saltz, Leonard B.
Background: Data on the outcomes of intensive care unit (ICU) admissions for patients with advanced incurable chemoresistant solid tumor malignancies, and the benefits of subsequent/post-ICU anticancer treatments are limited but have end-of-life and ethical implications. Methods: An institutional database was queried to identify patients of the gastrointestinal (GI) medical oncology service of Memorial Sloan Kettering Cancer Center with ≥1 ICU admission during 2014. Records were reviewed for evidence of cancer control from cancer treatment after the ICU admission. Results: Twenty-eight patients who had progressed beyond at least first-line chemotherapy for metastatic GI adenocarcinoma were admitted to the ICU for sequelae of progressive clinical deterioration. The most frequent reasons for ICU admission were sepsis (39%) and acute respiratory failure (29%). Ten patients died in the ICU, 3 died during the same hospitalization after ICU discharge, and 15 were discharged from the hospital. Of these 15, the median survival from hospital discharge was 2.2 months and 6 received further chemotherapy but with no evidence of clinical benefit. Of these 6, 3 lived over 5 months but the treatment of 5 entailed recycling of previously ineffective chemotherapy agents (3) or those originally used in the adjuvant setting (2). Two of these patients received liver-directed therapy without benefit. Conclusions: Admissions to the ICU in this cancer population were associated with high morbidity and mortality and did not result in benefit from subsequent cancer treatment. These data can be used to help establish realistic expectations and care goals in previously treated patients having metastatic GI cancer with clinical deterioration.